2007
DOI: 10.1111/j.1600-6143.2007.01927.x
|View full text |Cite
|
Sign up to set email alerts
|

A Synthetic Mechano Growth Factor E Peptide Enhances Myogenic Precursor Cell Transplantation Success

Abstract: Myogenic precursor cell (MPC) transplantation is a good strategy to introduce dystrophin expression in muscles of Duchenne muscular dystrophy (DMD) patients. Insulin-like growth factor (IGF-1) promotes MPC activities, such as survival, proliferation, migration and differentiation, which could enhance the success of their transplantation. Alternative splicing of the IGF-1 mRNA produces different muscle isoforms. The mechano growth factor (MGF) is an isoform, especially expressed after a mechanical stress. A 24 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 85 publications
(123 reference statements)
0
42
0
2
Order By: Relevance
“…Similar to the results derived from human cell lines, studies using animal cell lines models have shown that exogenous administration or overexpression of synthetic peptides, generated from different regions within the E domain of human (Ec) (28,31,33,145,146), trout (Ea) (144,147) or rodent (Ea and Eb) sequences (38) in human, rodent or porcine cells in culture showed unique though inconsistent effects in promoting cell proliferation and migration, and in delaying or inhibiting cell differentiation. In particular, actions associated with peptides derived from mammalian Ea domain have only recently been established, with rodent Ea-peptide reported to possess bioactivity (38).…”
Section: Igf-i Peptides Actions and Signalingmentioning
confidence: 50%
See 3 more Smart Citations
“…Similar to the results derived from human cell lines, studies using animal cell lines models have shown that exogenous administration or overexpression of synthetic peptides, generated from different regions within the E domain of human (Ec) (28,31,33,145,146), trout (Ea) (144,147) or rodent (Ea and Eb) sequences (38) in human, rodent or porcine cells in culture showed unique though inconsistent effects in promoting cell proliferation and migration, and in delaying or inhibiting cell differentiation. In particular, actions associated with peptides derived from mammalian Ea domain have only recently been established, with rodent Ea-peptide reported to possess bioactivity (38).…”
Section: Igf-i Peptides Actions and Signalingmentioning
confidence: 50%
“…Thus, during the last decade, many in vitro and in vivo studies have investigated the aspect of the differential IGF-I isoforms or their E-peptides actions in various conditions and pathologies (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). This concept was further supported by recent findings which revealed differential, E-peptide-or IGF-I isoform-specific signaling (31,33,34,(38)(39)(40).…”
Section: Introductionmentioning
confidence: 51%
See 2 more Smart Citations
“…When the predominant idea in this field was that the "lack of migration ability" was the key factor to explain the local fusion of the grafted cells, several studies attempted to attack this problem by inducing in the grafted myoblasts the secretion of enzymes that are crucial for the intratissular motion of cells by degrading the extracellular matrix [133][134][135][136][137][138]. Some of these studies reported an improved migration of myoblasts under particular experimental conditions in vitro and in vivo in mice.…”
Section: Increasing the Engraftment Of Myogenic Cellsmentioning
confidence: 99%